What is quality childcare? [videorecording] - Hilliard, Asa G.; National Association for the Education of Young Children; South Carolina Educational Television Network (Washington, D.C. National Association for the Education of Young Children [distributor], 1983)
An address by Asa G. Hilliard discussing the question of why our society is not child oriented and what can be done to improve the quality of education for all children.
"A production of the South Carolina Educational Television Network for National Association for the Education of Young Children."
Keywords: Day care centers; Education, Preschool